2019
DOI: 10.3390/antiox8100439
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant, Anti-Biofilm, and Solar Protection Activities of Melocactus zehntneri (Britton & Rose) Pulp Extract

Abstract: Cactaceae plants are important due to their nutritional and therapeutic values. This study aimed to identify the phytochemical profile and biological activities of six Melocactus zehntneri pulp extracts: hexane extract (HE), chloroform extract (CE), ethanol extract (EE), methanol extract (ME), final water extract (FWE), and water extract (WE). Sugar, phenolic compounds, and protein content of the extracts were determined. Then thin layer chromatography (TLC) was performed to detect the presence of terpenes (ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…The antioxidant activity of AsRE was evaluated in three stages: initiation (Total Antioxidant Capacity, power reducing and DPPH radical scavenging), propagation (cupric and ferric chelating), and termination (hydroxyl radical scavenging) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant activity of AsRE was evaluated in three stages: initiation (Total Antioxidant Capacity, power reducing and DPPH radical scavenging), propagation (cupric and ferric chelating), and termination (hydroxyl radical scavenging) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al [ 50 ] showed the activity of flavonoids from Carex meyeriana on scavenging the hydroxyl radical. Melocactus zehntneri ethanolic extract containing phenolic compounds, saponins and polysaccharides showed 100% hydroxyl scavenging activity for polar extract (using 100 µg/mL), whereas the non-polar extracts showed an activity of around 20% [ 46 ]. Therefore, AsRE exerted their antioxidant activity in three stages: initiation, propagation and termination.…”
Section: Discussionmentioning
confidence: 99%
“…Their methanol extracts showed a higher free radical scavenging activity (66.37%) than the analyzed cacti at an extract concentration of 10 mg/mL [ 30 ]. Likewise, pulp extracts from the stems of the Brazilian cactus Melocactus zehntneri also showed a depurating activity of DPPH with approximately 60% of activity [ 31 ]. Specifically, for the genus Mammillaria , lower values ranging between 4–10 mg of Trolox equivalent/g sample with ethanol extracts of different species of that genus were reported [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite several studies about the antibiofilm effect of these phytochemicals, little is known about their mechanisms of action against biofilms. 236–238 However, in the case of thymol, some authors have demonstrated the ability of this compound to interfere with QS and cell motility. 239–241…”
Section: Phytochemicals As Antibiofilm Agents: Biological and Biochem...mentioning
confidence: 99%